Dextran Sulfate Sodium Effectiveness As Inflammatory Bowel Disease Inducer In BALB/c Mice - Hanina Hanina; Lipinwati Lipinwati; Tia Wida Ekaputri Hz; Hasna Dewi (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
ABSTRACT Background: Inflamatory Bowel Disease (IBD) in animal model could be induced by chemical agents such as dextran sulfate sodium (DSS), Â trinitrobenzene sulfanic acid and oxazolone. The inflammation induced by DSS gave many clinical symptoms and immnulogic reactions like in human. In the recent study, the disease activity index has been assessed on the BALB/c mice that induced by DSS 2% and 3%, the result was no significant result. Therefore, DAI score was not necessarily describe the intestinal tissue real condition, so the researcher want to continue assessing DSS influence to the microscopic features of BALB/c mice intestine and colon. Methods: Nine male BALB/c mice 6-8 weeks, weight 25-40 g divided in 3 groups. Group I as control, while group II and III induced by Â 2 cycles of 2% DSS for 5 days followed by drinking water for 10 days and 3 cycles of 3% DSS for 7 days followed by drinking water for 7 days. Assesment of DSS effectiveness by microscopic examination of intestine and colon to observe inflammatory features. Results: . The microscopic features of group II and group III mice intestine and colon has no inflammatory features as control group. Oral admission DSS 2% and DSS 3% did not establish microscopic changes in BALB/c mice intestine and colon, so it was not effective as mice IBD inducer. Â